A novel method for overcoming the impact of spatially varying ambient magnetic fields on a DC magnetic field-based tracking system. (2nd January 2016) - Norrdine, Abdelmoumen; Kasmi, Zakaria; Blankenbach, Jörg
Abstract : A magnetic indoor local positioning system enables positioning in harsh environments due to the advantageous characteristics of magnetic signals such as penetrating of various obstacles and robustness against fading effects. Nevertheless, the indoor tracking remains a challenge, due to the non-stationary property of the ambient magnetic fields, signal transients and eddy current effects. In this paper, we propose a method, which is based on zero velocity detection, in order to overcome the mentioned constraints by the pedestrian tracking.